2020
DOI: 10.1002/cnma.201900733
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to the Synthesis of a Two‐Dimensional Polymer Using a Preorganized Host‐Guest Network by Self‐Assembly at the Liquid/Solid Interface

Abstract: An approach to synthesize a two‐dimensional polymer (2DP) using a preorganized host‐guest network at the liquid/solid interface is presented. As a host network, we used a self‐assembled monolayer of a dehydrobenzo[12]annulene derivative having aminophenyl groups at three alkoxy chain ends and, as a guest, a hexakis(phenylethynyl)benzene derivative having six formyl groups, aiming to connect the host to the guest embedded in the host matrix by imine bond formation. STM observations of host‐guest mixtures with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…33,34 During the on-surface reaction process, new molecules would be produced in situ and form new selfassembled architectures. 35,36 Thus, plentiful efforts have been made to investigate the on-surface synthesis of chemical molecules during these years, for example, the Schiff-based reaction, 37−39 Glaser reaction, 40−42 Ullmann coupling reaction, 43−45 photochemical reaction, 15,46 Knoevenagel reaction, 33 and so forth. 47 With the help of on-surface reactions, various self-assembled covalent structures have been successfully constructed on the 2D substrate.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…33,34 During the on-surface reaction process, new molecules would be produced in situ and form new selfassembled architectures. 35,36 Thus, plentiful efforts have been made to investigate the on-surface synthesis of chemical molecules during these years, for example, the Schiff-based reaction, 37−39 Glaser reaction, 40−42 Ullmann coupling reaction, 43−45 photochemical reaction, 15,46 Knoevenagel reaction, 33 and so forth. 47 With the help of on-surface reactions, various self-assembled covalent structures have been successfully constructed on the 2D substrate.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It is necessary to note the balance is not immutable, and a series of elements will influence the self-assembled nanostructures, for instance, molecular concentration, light irradiation, temperature, solvent polarity, and so on. , Under some special circumstances, the self-assembled molecular structures could be transformed much more easily, such as the on-surface reaction. , In addition, the nanostructures formed by on-surface reaction are more thermodynamically and chemically stable and undergo the breakage and reformation of the covalent bonds. , During the on-surface reaction process, new molecules would be produced in situ and form new self-assembled architectures. , Thus, plentiful efforts have been made to investigate the on-surface synthesis of chemical molecules during these years, for example, the Schiff-based reaction, Glaser reaction, Ullmann coupling reaction, photochemical reaction, , Knoevenagel reaction, and so forth . With the help of on-surface reactions, various self-assembled covalent structures have been successfully constructed on the 2D substrate. ,, Furthermore, the intermediate products of the reaction are capable of being clearly detected by the actual-time and in situ STM characterization, which helps to elucidate the reaction principles of the molecular nanoarchitectures on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular geometry changes accompanying on-surface reactions can alter the packing contacts that determine monolayer morphology. There are examples of molecular monolayers that accommodate these reaction-induced structural changes and transform efficiently into macromolecular monolayers. The packing constraints present in other molecular assemblies inhibit or permit only partial postassembly polymerization . The monolayers investigated here seek to isolate “morphology-determining” and “reactivity” functions into physically and spatially independent substructures.…”
Section: Introductionmentioning
confidence: 99%
“…16−18 The packing constraints present in other molecular assemblies inhibit 19 or permit only partial postassembly polymerization. 20 The monolayers investigated here seek to isolate "morphology-determining" and "reactivity" functions into physically and spatially independent substructures. The assembling molecules (Figure 1) contain triphenyleneethynylene (TPE) triaryl cores with one hexadecyloxy (n-C 16 H 33 O) chain at the para-position of each terminal aryl ring and two terminal alkynyl chains on the central aryl ring (core chains).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Scanning tunneling microscopy (STM) with atomic resolution is considered to be the most effective method to investigate the molecular dynamics of assembly at solid/liquid interfaces, and the regulation behavior of guest molecules, which impact the host molecules can be observed in real-time by STM under an ambient environment. Hou et al used STM to detect porphyrin derivatives with side chain groups not only to obtain a self-assembled structure of H 2 TCPp under the action of hydrogen bonds but also to successfully regulate the host molecule by introducing dipyridine as a guest molecule . Although some studies on pyridine regulation on self-assemblies of porphyrin derivatives have been reported, this article introduces a co-assembled structure formed by the interaction of different hydrogen bonds and different pyridine derivatives including terpyridine.…”
Section: Introductionmentioning
confidence: 99%